Task force on Physician's Assistant programs [for LCME] - Correspondence: Rice to Kinney - Rice, Walter G. (1970)
This memorandum dated July 30, 1970 was sent to Dr. Thomas Kinney at Duke University by Dr. Walter Rice, Acting Secretary, Liaison Committee on Medical Education (LCME) requesting Kinney "to serve on the newly created Task Force on Physician's Assistant Programs under the auspices of the LCME." The task force originated from the AAMC Council of Academic Society who had established a previous task force to "consider the role of these assistants and the need for standards for programs producing them." A copy of the AAMC task force report is attached to the memorandum for information. A meeting is scheduled for October 7, 1970.